Netizens Perceptions of The Announcement About The New Normal Policy: Content Analysis of WHO Indonesia Instagram Account - Mardani, Puri Bestari; Febiana Christanti, Maria; Ripa’i Sutowo, Irpan (International Journal of Social Service and Research, 2021)
Covid 19 virus still exists. However, social distancing has begun to be less stringent in several countries, including Indonesia. One of the reasons is to revive the economy that is starting to weaken. It brings the Indonesian Government to followed the WHO direction to implement New Normal. Various information about New Normal is starting to spread through many media channels, one of them is the Instagram account of @whoindonesia. Many comments from the account followers filled the comment box and not al ofl them were positive. This study aims to map various responses through the content analysis method. The purpose is to find out the netizens’ perception of the New Normal. If the netizens understanding is different or not in accordance with the objective of The New Normal policy, then this policy might have a risk in increasing the covid-19. The result of this study is to provide an overview to policymakers about the characteristics of the audience they face in order to be able to determine the right communication strategy in reaching and providing understanding to them